The UK Innocence Movement: Past, Present, and Future? - Holly Greenwood (Understanding Wrongful Conviction: The protection of the innocent across Europe and America, 2015)
This chapter drew on original empirical data to explore the state of ‘UK innocence movement’, which refers to the development and operation of innocence projects (hereafter IPs) across the UK. This was the first research to examine IPs in the UK and was funded by the Economic and Research Council. IPs originated in the United States and are typically university based clinics in which law students investigate claims of alleged miscarriages of justice. Approximately 38 IPs were established in the UK between 2004 and 2014; the rapid spread of such projects has led to this being referred to as the 'UK innocence movement'. The combination of a trend towards clinical legal education in the UK and the rapidly increasing number of IPs suggested that the UK innocence movement was going from strength to strength. However, by 2014, after ten years in operation, IPs had only ever had three cases referred to the Court of Appeal and these were from only two universities; furthermore, in the summer of 2014, Michael Naughton announced he would be closing the Innocence Network UK (INUK) as a membership organisation for IPs. This marked the beginning of a period of instability and uncertainty for UK IPs as many relied on INUK to screen suitable cases, to provide training and to set national standards. This chapter was written in 2015, which was a critical time for the UK ‘innocence movement’. Drawing on 19 semi-structured interviews with leaders of IPs and other similar clinics, this chapter discusses the origins of the UK innocence movement, reflects on its position in 2015, and then considers the future landscape for IPs. This chapter discusses a number of problems that participants identified with the UK movement, including systemic challenges, difficulties within the network, and tensions within the IP model. It illustrates how despite a decline in the number of university IPs, there were many intending to continue; and that rather than seeing this as a period of decline, many participants saw this as a period of evolution. This chapter concludes that the future might see a phasing out of the IP model, but this would be replaced with a new emerging model of university miscarriage of justice clinics.